2015
DOI: 10.1371/journal.pone.0122169
|View full text |Cite
|
Sign up to set email alerts
|

Population-Level Scale-Up of Cervical Cancer Prevention Services in a Low-Resource Setting: Development, Implementation, and Evaluation of the Cervical Cancer Prevention Program in Zambia

Abstract: BackgroundVery few efforts have been undertaken to scale-up low-cost approaches to cervical cancer prevention in low-resource countries.MethodsIn a public sector cervical cancer prevention program in Zambia, nurses provided visual-inspection with acetic acid (VIA) and cryotherapy in clinics co-housed with HIV/AIDS programs, and referred women with complex lesions for histopathologic evaluation. Low-cost technological adaptations were deployed for improving VIA detection, facilitating expert physician opinion, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
142
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 132 publications
(147 citation statements)
references
References 26 publications
4
142
1
Order By: Relevance
“…Six studies were carried out in Brazil [13,14,15,16,17,18] and four in the United States [19,20,21,22] . There was only one article from each of the following countries: Argentina [23] , Australia [24] , Canada [25] , England [26] , Italy [27] , Malawi [28] , Zambia [29] and United Kingdom [30] . Thus, the final sample comprised 18 articles.…”
Section: Characterizing the Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Six studies were carried out in Brazil [13,14,15,16,17,18] and four in the United States [19,20,21,22] . There was only one article from each of the following countries: Argentina [23] , Australia [24] , Canada [25] , England [26] , Italy [27] , Malawi [28] , Zambia [29] and United Kingdom [30] . Thus, the final sample comprised 18 articles.…”
Section: Characterizing the Studiesmentioning
confidence: 99%
“…With regard to the treatment and diagnostic of precursor lesions identified in the target population, data from three Brazilian [16,18,17] , one Zambian [29] and one British studies [26] were identified.…”
Section: International Journal For Innovation Education and Research mentioning
confidence: 99%
See 1 more Smart Citation
“…2017;6(3-4):58-64 services, particularly in many sub-Saharan African countries. This approach has been shown to be acceptable, safe, efficacious and feasible in demonstration projects and large-scale national or regional programs are on-going in countries such as Thailand and Zambia [4,6,7,[17][18][19][20]. Recently a screen-andtreat approach using thermal coagulation has been evaluated in a large screen-and-treat field program in Malawi, in which thermal coagulation for treatment of VIA-positive lesions was introduced as an alternative to cryotherapy [21].…”
Section: Nessa Et Al J Clin Gynecol Obstet 2017;6(3-4):58-64mentioning
confidence: 99%
“…Simultaneously implementing contextually-appropriate screening and early detection programs for such priority cancers, alongside the scale-up of cancer surgery service platforms, and tightly linking positive screening results to diagnostic and treatment interventions, is a necessity. Examples of such interventions in the women's cancers domain include "screen and treat" using VIA (visual inspection of the cervix using acetic acid) and cryotherapy/cold coagulation/loop electrosurgical excision procedure for cervical cancer prevention [22]; and clinical breast examination and ultrasound-guided biopsy of palpable breast masses for breast cancer early detection. Initially choosing only a few sites (and aiming for those with the best infrastructure, adequate levels of human resources and highest burden of disease) for testing the scale-up model would facilitate success.…”
Section: Start By Doing What's Best Easiest and Most Impactfulmentioning
confidence: 99%